Effect of indomethacin on binding of bilirubin to albumin. - Lam, B C (1990)
The effect of indomethacin on the binding of bilirubin to protein was studied in vitro by the horseradish peroxidase oxidation method. Plasma indomethacin concentrations ranging from 1500 micrograms/l to 4500 micrograms/l, which were much higher than the therapeutic concentrations achieved in vivo, were used for the studies. The bilirubin-protein titration curves obtained indicate that indomethacin, although protein bound, does not affect the binding of bilirubin to protein. Our study confirms that it is safe to use conventional doses of indomethacin in jaundiced preterm infants.